Interaktivitas Media Sosial Facebook Axe dan Dove dalam Perspektif Gender - Widyastuti, Dhyah Ayu Retno; Ratriyana, Ina Nur (Jurnal ILMU KOMUNIKASI, 2017)
The objective of this research was to review an interactivity on Facebook accounts of brand Axe and Dove. The interactivity itself has been analyzed using content analysis method. The finding of the research were (1) Facebook account consists of advertising campaign; (2) The messages  involve of verbal and non-verbal messages; (3) The audiences respond showed positive, negative, and neutral responses; (4) The number of audiences respond were dominated by male on Axe account and female for Dove account. The tendency of female responses were communicative and active. Meanwhile, the male responses were passive, weak, and communicative.